2010
DOI: 10.1111/j.1398-9995.2010.02478.x
|View full text |Cite|
|
Sign up to set email alerts
|

The CKLF1-C19 peptide attenuates allergic lung inflammation by inhibiting CCR3- and CCR4-mediated chemotaxis in a mouse model of asthma

Abstract: Thus, C19 can attenuate airway eosinophilia and lung inflammation by inhibiting CCR3- and CCR4-mediated chemotaxis in a mouse model of asthma. Given its ability to inhibit human CCR3- and CCR4-meditated chemotaxis, C19 has great therapeutic potential for use in the treatment and control of allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…C19 has weaker chemotactic activity and inhibits chemotaxis induced by CKLF1 or thymus and activation-regulated chemokine (CCL17) [29]. C19 can be used to treat asthma as a CKLF1 antagonist [30]. Previously, we have shown that treatment with C19 decreased the infarct size and water content [14].…”
Section: Discussionmentioning
confidence: 99%
“…C19 has weaker chemotactic activity and inhibits chemotaxis induced by CKLF1 or thymus and activation-regulated chemokine (CCL17) [29]. C19 can be used to treat asthma as a CKLF1 antagonist [30]. Previously, we have shown that treatment with C19 decreased the infarct size and water content [14].…”
Section: Discussionmentioning
confidence: 99%
“…62 CCR8 is a more specific T H 2-associated receptor but is also expressed on regulatory T cells. 63 Tian et al 64 showed in a murine model of asthma that a human chemokine-like factor 1 C-terminal peptide (C19), which blocks the function of the chemokine receptor CCR4, reduced airway eosinophilia and airway hyperresponsiveness. There are no reports of the antagonists of any of these receptors in asthmatic patients.…”
Section: Antagonists Of Adhesion and Chemokine Pathways Controlling Ementioning
confidence: 99%
“…The number of eosinophils in the nasal mucosa was counted at a magnification of × 400 within five fields [3]. The severity of peribronchial and perivascular inflammation was scored according to a published guideline [11].…”
Section: Histologic Analysismentioning
confidence: 99%